2021
DOI: 10.3389/fgwh.2021.697607
|View full text |Cite
|
Sign up to set email alerts
|

Community-Engaged Approaches to Cervical Cancer Prevention and Control in Sub-Saharan Africa: A Scoping Review

Abstract: Background: Cervical cancer remains one of the top causes of cancer mortality among African women. Cervical cancer screening and early detection and treatment of precancer is one of the evidence-based interventions to reduce incidence and mortality. The application of community-based participatory research (CBPR) has been used in the United States to improve participation in screening and reduce cervical cancer disparities. However, it is unclear whether these engaged approaches have been used in sub-Saharan A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It was also revealed that the disruption imposed by cervical cancer on social and economic aspects of patients’ life was a source of constant stress, low self-esteem, and isolation [ 14 , 32 ]. This finding in the current study implies that healthcare providers should conduct a regular individualized assessment to explore patients’ social and financial needs to ascertain the extent of socio-economic disruptions for early and proper linkage to social support groups [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also revealed that the disruption imposed by cervical cancer on social and economic aspects of patients’ life was a source of constant stress, low self-esteem, and isolation [ 14 , 32 ]. This finding in the current study implies that healthcare providers should conduct a regular individualized assessment to explore patients’ social and financial needs to ascertain the extent of socio-economic disruptions for early and proper linkage to social support groups [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen were excluded because they did not report a history of anal sex with another male partner. Descriptive analyses found that 307 (38.4%) were aged $35 years, with a median (interquartile range [IQR]) age of 32 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) years, and 297 (27.1%) received HIV clinical care at TRUST. Of the 297, 200 (67.3%) were first diagnosed with HIV at TRUST.…”
Section: Resultsmentioning
confidence: 99%
“…22 Screening guidelines are under development and will eventually be forthcoming worldwide. Existing literature from SSA highlights disparities in accessing secondary prevention, such as colorectal 23,24 and cervical 25,26 cancer screening, and similar patterns may emerge for anal cancer. Thus, additional consideration of this area is timely to best ensure its future implementation and proper adherence.…”
Section: Introductionmentioning
confidence: 94%
“…Finally, our process emphasizes the importance of community-based participatory research, an approach that has been widely applied to studies across the cancer continuum, 40 including global settings. 41 Although the study team for this project included members of the local community with years of experience providing care to this population, a thorough approach to pilot testing revealed many unanticipated barriers to survey administration. All survey instruments, particularly those involving Likert scales, should be not only translated but also culturally adapted and carefully tested in research settings.…”
Section: Discussionmentioning
confidence: 99%